Anglican theological review ([Evanston, Ill., Anglican Theological Review], 1918)
"A New Testament bibliography for 1914 to 1917 inclusive", by Frederick C. Grant: v. 1, p. [58]-91.
"An Old Testament bibliography for 1914 to 1917 inclusive", by H.C. Ackerman: v. 1 <p. [214]-237, [314]-332,>
Academic Journal
Online version of print publication.
Vols. 11-20 in v. 20; Vols. 31-40 in v. 40.
Keywords: Theology -- Periodicals